Pemikiran Ibnu Qayyim Al Jauziyyah Tentang Pendidikan Anak Usia Dini - Fitri Ramadhini (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2021)
In this research, the background is how to educate children from an early age. In educating early childhood is one that must be developed with all its potential. Therefore,in the scope of the family in early childhood, he gets his first education is  both  parents,  who  have  been  given  the  mandate  also  responsibility.  But  the reality  is  sometimes  parents  lack  interaction  with  their  children  and  also  their sense of caring. So that children also do not have a good interaction with parents, families, people, and  the environment. The method used in research is the method of  library  research  (Library  Research), with a  qualitative  approach.  Of  the problems  discussed,  the  researcher  uses  a  philosophical  approach.  So  that  the object  of  research  is  the  thought  of  early  childhood  education  according  to  Ibnu Qayyim Al Jauziyyah.  In  data  collection  techniques,  the  researchers  used documentation materials. And the researchers themselves are the core instrument. Researchers use content analysis (content analysis). Based on the results of early childhood education research according  to  Ibn  Qayyim's  thinking  is  very important  for  children's  education  from  an  early  age.